2012
DOI: 10.2478/v10011-012-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Senile Cataract Maturity on Blood Oxidative Stress Markers and Glutathione-Dependent Antioxidants: Relations with Lens Variables

Abstract: The Impact of Senile Cataract Maturity on Blood Oxidative Stress Markers and Glutathione-Dependent Antioxidants: Relations with Lens VariablesOxidative stress is implicated in senile cataract (SC) genesis, although the impact of SC maturity on blood oxidative stress markers is unclear. Total hydroperoxides, malondialdehyde (MDA), glutathione (GSH), glutathione peroxidase (GPx), glutathione reductase (GR) and glutathione S-transferase (GST) were measured in the blood and lens samples of patients having either i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The other reason is that in SC the antioxidant genes can be markedly downregulated, 29 and the progression of SC has already been associated with decreased GPx activity, both at local and systemic level. 2,3 Furthermore, lenses of acatalasemic mice were demonstrated to be almost as efficient in degrading the H 2 O 2 ex vivo as those of the wild type, 30 indicating that CAT itself may not be of critical importance for prevention of lens oxidative damage. In the current study, the average CAT activity in AH was 32 pmol/ml, and was unrelated to oxidative stress status and, as in a previous study, 5 unaffected by cataract maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other reason is that in SC the antioxidant genes can be markedly downregulated, 29 and the progression of SC has already been associated with decreased GPx activity, both at local and systemic level. 2,3 Furthermore, lenses of acatalasemic mice were demonstrated to be almost as efficient in degrading the H 2 O 2 ex vivo as those of the wild type, 30 indicating that CAT itself may not be of critical importance for prevention of lens oxidative damage. In the current study, the average CAT activity in AH was 32 pmol/ml, and was unrelated to oxidative stress status and, as in a previous study, 5 unaffected by cataract maturity.…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that excess levels of ocular oxidants can cause damage to the lens and other tissues, which are implicated in normal ageing process and in pathogenesis of several eye diseases, such as pseudoexfoliation syndrome, diabetic retinopathy, glaucoma, and senile cataract (SC). [1][2][3][4][5][6][7] The toxicity of oxidants depends on their ability to induce cross-linking, aggregation, fragmentation, and insolubilization of structural proteins, inactivation of enzymes, and lipid peroxidation (LPO) of the membrane-bound polyunsaturated fatty acids (PUFA), leading to impaired cell function, apoptosis, and necrosis. 1,2 Unlike ocular tissues, AH contains only small quantities of proteins and antioxidant enzymes, and its antioxidant defense thus relies on unusually high levels of low-molecular weight antioxidants, mostly ascorbic acid, present at the level of B1 mM, even in SC.…”
Section: Introductionmentioning
confidence: 99%
“…Malondialdehyde (MDA), a lipid peroxidation product, is considered a biomarker. An increase in MDA serum levels in patients with senile cataracts has been reported [208][209][210][211]. Studies performed in humans and animals concluded the increment in lens MDA concentration was higher in diabetic cataracts than in senile non-diabetic cataracts [212,213].…”
Section: Cataractsmentioning
confidence: 99%
“…Studies performed in humans and animals concluded the increment in lens MDA concentration was higher in diabetic cataracts than in senile non-diabetic cataracts [212,213]. In addition, plasma glutathione peroxidase (GPx) and hydroperoxides seem to be associated with the severity of the cataract [211].…”
Section: Cataractsmentioning
confidence: 99%
See 1 more Smart Citation